2007
DOI: 10.1590/s1020-49892007000700005
|View full text |Cite
|
Sign up to set email alerts
|

A rubella serosurvey in postpartum women in the three regions of Peru

Abstract: The proportion of postpartum women at the study sites who were found to be susceptible to rubella was 12.8%, placing Peru among the countries facing a moderate level of risk for the occurrence of CRS cases. The findings suggest the need to also provide the rubella vaccine to other population groups, especially women of childbearing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In locations that are weakly coupled to the metapopulation, regular local extinction resulting from the high CCS of rubella [12] will be followed by prolonged periods without re-introduction, which will allow susceptible individuals to leak into older age classes [10]. In agreement with this, a survey of sero-negativity in post-partum women in Peru identified considerable geographical structure, with much higher sero-negativity in the distant forest locations than in the costal region around Lima [30]. Additionally, CRS incidence in hospitals in, for example, Loreto, the weakly coupled province in the northeast of the country, are also high relative to central and coastal locations [31].…”
Section: Discussionmentioning
confidence: 97%
“…In locations that are weakly coupled to the metapopulation, regular local extinction resulting from the high CCS of rubella [12] will be followed by prolonged periods without re-introduction, which will allow susceptible individuals to leak into older age classes [10]. In agreement with this, a survey of sero-negativity in post-partum women in Peru identified considerable geographical structure, with much higher sero-negativity in the distant forest locations than in the costal region around Lima [30]. Additionally, CRS incidence in hospitals in, for example, Loreto, the weakly coupled province in the northeast of the country, are also high relative to central and coastal locations [31].…”
Section: Discussionmentioning
confidence: 97%
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%